An Approximation Algorithm for The Load-Balanced Clustering Problem in Wireless Sensor Networks - Chor Ping Low; Jim Mee Ng; Yew Hock Ang (Proceedings of 15th International Conference on Computer Communications and Networks, 2006)
Wireless sensor networks have been receiving increasing attention in recent years due to their potential applications in the establishment of dynamic communications for emergency/rescue operations, disaster relief efforts, and military networks. In this paper, we investigate the problem of grouping the sensor nodes into clusters to enhance the overall scalability of the network. A selected set of nodes, known as gateway nodes, will act as cluster-heads for each cluster and the objective is to balance the load among these gateways. Load balanced clustering increases system stability and improves the communication between the various nodes in the network. We call the problem addressed in this paper as the load-balanced clustering problem (LBCP). We prove that LBCP is NP-hard and we proposed an efficient 3/2-approximation algorithm for the problem.